Implementation of a Project Methodology in teaching technology education, a fundamental tool for scientific-technological reflection - Nelson Oyarzún Oyarzún (Corporación Universitaria Minuto de Dios, 2015)
The article presents a project-methodology applied to teaching all academic programs in Basic Education as General Education in Basic Education with a minor in Mathematics and Science at the Universidad de Los Lagos, Chile. The aim is to show how this methodology generates a scientific-technological reflection of students. The results obtained indicate two technological progresses in scientific thinking of students in General Basic Education. Contrasted with a case whereby only some phases of the project-methodology were used, there was no enough exposure to yield a successful development of scientific-technological reflection. While observing classes, specific characteristics proper to traditional behaviorism were discovered as exemplified in a repeated behavior of oral exposure to the teacher. This project-based-methodology-study informs innovation and improvement with necessary elements to the teaching expertise. Among these necessary elements is the reflection on problematic situations, their analysis, the search for information and the stanch assessment of the most appropriate responses to the problem under treatment.